pH Induced structural alterations in an aspartic protease from Vigna radiata indicating an alkali induced molten globule state - Kulkarni, Aarohi; Gaikwad, Sushama M.; Rao, Mala (International Journal of Biological Macromolecules, 2008)
pH-dependent transitions in secondary and tertiary structure are described for a plant aspartic protease from Vigna radiata. The enzyme was pH stable with pH optima of 3.0. The Lineweaver Burk analysis at various pH yielded pK(a) values of 3.3 and 4.29 indicating acidic amino acids at the active site of the enzyme. The structural changes exemplified compact secondary structure collapsed tertiary structure and exposure of hydrophobic patches at pH 10. The changes at pH 10 are typical of a molten globule state. This alkali induced molten globule is novel since acid induced molten globule state is more reported. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Alkali induced molten globule; Plant aspartic protease; Structural transitions